African isolates show a high proportion of multiple copies of the Plasmodium falciparum plasmepsin-2 gene, a piperaquine resistance marker - (:unkn) unknown (My University, 2019)
Background: Today, the development of new and well-tolerated anti-malarial drugs is strongly justified by the emergence of Plasmodium falciparum resistance. In 2014–2015, a phase 2b clinical study was conducted to evaluate the efficacy of a single oral dose of Artefenomel (OZ439)–piperaquine (PPQ) in Asian and African patients presenting with uncomplicated falciparum malaria.Methods: Blood samples collected before treatment offered the opportunity to investigate the proportion of multidrug resistant parasite genotypes, including P. falciparum kelch13 mutations and copy number variation of both P. falciparum plasmepsin 2 (Pfpm2) and P. falciparum multidrug resistance 1 (Pfmdr1) genes.Results: Validated kelch13 resistance mutations including C580Y, I543T, P553L and V568G were only detected in parasites from Vietnamese patients. In Africa, isolates with multiple copies of the Pfmdr1 gene were shown to be more frequent than previously reported (21.1%, range from 12.4% in Burkina Faso to 27.4% in Uganda). More strikingly, high proportions of isolates with multiple copies of the Pfpm2 gene, associated with piperaquine (PPQ) resistance, were frequently observed in the African sites, especially in Burkina Faso and Uganda (> 30%).Conclusions: These findings were considered to sharply contrast with the recent description of increased sensitivity to PPQ of Ugandan parasite isolates. This emphasizes the necessity to investigate in vitro susceptibility profiles to PPQ of African isolates with multiple copies of the Pfpm2 gene and estimate the risk of development of PPQ resistance in Africa.
Keywords: African Research